Cultura financiera en los estudiantes del quinto nivel de la carrera de contabilidad UNAP 2019 - Nuñez Tuanama, Katerin Silene (2021)
According to the Superintendency of Banking and Insurance indicates that less than 5% of Peruvians have knowledge about financial education, citizens often make hasty financial decisions without much knowledge or information, the objective of this Research was to determine the level of financial culture in The students of the fifth level of the accounting school, UNAP, 2019, for this, the present descriptive research and non-experimental design was carried out, determining the level of education and financial planning, identifying that financial education in the The study population has a satisfactory level since 100% of the participants recognized the importance of the personal budget, the prioritization of their expenses, the control of income and expenses and the importance of savings, in relation to financial planning it was identified that the participants show a satisfactory level since 56% practice saving, 96% have They have the desire to invest and 60% plan the number of installments when they use their credit card and on average more than 50% of the students of the fifth level of the professional accounting school, UNAP, 2019 have a Satisfactory Financial Culture.